Effects of soil compaction on seedling morphology, growth, and architecture of chestnut-leaved oak (Quercus castaneifolia) - Jourgholami M; Khoramizadeh A; Zenner EK (iForest - Biogeosciences and Forestry, 2017)
Soil compaction following traffic by heavy-timber harvesting machinery usually causes an increase in soil strength, that is a stress factor negatively affecting the growth of newly germinated seedlings. This study used a soil strength experiment carried out in a greenhouse to test the hypotheses that increasing soil strength would adversely affect seedling morphology and alter seedling architecture by changing biomass allocation patterns. We explored the effects of soil compaction in a loam to clay-loam textured soil with optimal conditions of water on a continuous scale (0.2-1.0 MPa penetration resistance) on growth responses of the deciduous Quercus castaneifolia (C.A.Mey). Both above- and below-ground seedling characteristics, including size and biomass, were negatively affected by soil compaction. At the highest intensity of compaction, size and growth were reduced by 50% compared to controls; negative effects were typically more severe on below-ground (i.e., the length and biomass of the root system) than on above-ground responses. Increasing soil strength did not change above- and below-ground biomass allocation patterns (i.e., root mass ratio, root:shoot ratio, specific root length), resulting in unchanged seedling architecture. Strong adverse effects were already evident in the low-intensity compaction treatment and no critical soil strength threshold was observed. We conclude that root and height growth in Q. castaneifolia seedlings is limited by any increase of soil strength, though no evidence for the disruption of a functional equilibrium between above- and below-ground plant portions was found up to soil strengths of 1.0 MPa, at least under optimal water supply.